Hubungan Pemberian Pekerjaan Rumah (PR) Dengan Motivasi Belajar Siswa Di MDTA Nurul Yaqin Bukit Cangang Kota Bukittinggi - Ansor Azhari Simanungkalit; Salmi Wati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research was motivated by the low learning motivation of students at MDTA Nurul Yaqin Bukit Cangang, Bukittinggi City. Low motivation to learn is thought to be related to giving homework. The problem formulation in this research is: Is there a significant relationship between giving homework and students' learning motivation? This research aims to find out whether there is a significant relationship between giving homework and students' learning motivation. The hypothesis in this research is that there is a significant relationship between giving homework and learning motivation. The type of research used is correlational research. The population of this research was all students, totaling 53 students with a sample of 43 students. This research data is in the form of a questionnaire regarding homework assignments and student learning motivation. The results of this research obtained r = 0.956 at a very high level. This shows that H0 is rejected or HI is accepted, which states that there is a significant relationship between giving homework and students' learning motivation. The relationship between giving homework and students' learning motivation is a very high relationship with a coefficient of determination value of 0.956.